2019
DOI: 10.3390/ijms20205023
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate an Old Drug with New Tricks

Abstract: Methotrexate (MTX) is the first line drug for the treatment of a number of rheumatic and non-rheumatic disorders. It is currently used as an anchor disease, modifying anti-rheumatic drug in the treatment of rheumatoid arthritis (RA). Despite the development of numerous new targeted therapies, MTX remains the backbone of RA therapy due to its potent efficacy and tolerability. There has been also a growing interest in the use of MTX in the treatment of chronic viral mediated arthritis. Many viruses—including old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
192
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(263 citation statements)
references
References 219 publications
(275 reference statements)
3
192
0
17
Order By: Relevance
“…MTX thus limits the viability of highly replicating cells. Moreover, MTX-induced reactive oxygen species generation modulates different cell functions, such as suppression of cytokine production and cell proliferation decreasing TNF-α, IL-1β, and adhesion molecules (E-selectin and VCAM-1) [183].…”
Section: Methotrexatementioning
confidence: 99%
“…MTX thus limits the viability of highly replicating cells. Moreover, MTX-induced reactive oxygen species generation modulates different cell functions, such as suppression of cytokine production and cell proliferation decreasing TNF-α, IL-1β, and adhesion molecules (E-selectin and VCAM-1) [183].…”
Section: Methotrexatementioning
confidence: 99%
“…It has been shown that the methotrexate treatment reduces the TNFα, IL1β, and IL6 production and increases the IL10 expression in the synovial tissue of rheumatoid arthritis patients [12]. At the same time, Pawlik et al (2006) established the interrelation of a number of the cytokine genes polymorphic loci variants with the level of phytohemagglutinin-stimulated secretion of the Table 3.…”
Section: Discussionmentioning
confidence: 98%
“…An important role in the regulation of inflammation, cell survival and proliferation is played by NFκB, a family of transcription factors (RelA (p65), cRel, RelB, NFκB1 (p50 and its precursor p105), and NFκB2 (p52 and its precursor p100)), which functions as various heteroor homodimers [12,36,37]. One of the key members of this family is p50 encoded by the NFKB1 gene.…”
Section: Response To Methotrexatementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the CANTOS trial, the clinical Cardiovascular Inflammation Reduction Trial (CIRT) targeted a broader range of pro-inflammatory processes using the anti-rheumatic compound methotrexate, which is known to reduce cytokine secretion and the generation of ROS [ 228 ]. After the primary prevention of rheumatoid arthritis, off-target effects such as a reduction in cardiovascular events were detected with the methotrexate treatment using the normal dosing range of 5–30 mg per week for rheumatoid arthritis [ 229 ].…”
Section: Controversial Outcome Of Rcts—explanatory Approachesmentioning
confidence: 99%